Sistem Informasi Praktek Kerja Industri bagi Siswa Kelas XII pada Sekolah SMK Kasimo Kererobbo - Margareta Dairo; Gergorius Kopong Pati; Maria Wilda Malo (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
The Industrial Internship (PKI) Information System for 12th-grade students at Kasimo Kererobbo Vocational School aims to simplify the process of managing and monitoring students' PKI activities in an efficient and structured manner. This system is designed to integrate various information related to PKI activities, from registration of partner companies, student placement, to reporting of PKI activity results. By using a web-based system, the administrative process becomes more transparent and can be accessed by students, supervising teachers, and partner companies in real-time. In addition, this system also allows monitoring of student progress during PKI and facilitates communication between the school and partner companies. The results of this system development are expected to improve the quality and effectiveness of PKI implementation, while simplifying administration that has been done manually. This system also makes it easier for students to choose partner companies that suit their majors and interests, and provides faster and more timely access to reports and evaluations of PKI results.